18F FDG PET-CT Imaging in the Evaluation of Diagnosed Extra Pulmonary Tuberculosis (Bangladesh Journal of Nuclear Medicine, 2019)
Objectives: Extra Pulmonary Tuberculosis (EPTB) presents with atypical symptoms and heterogeneous clinical features. Management of EPTB including diagnosis, localization, extension and monitoring treatment response of active disease is quite challenging. Moreover, localization of active disease, differentiation between active and latent disease by conventional methods is troublesome. So this study was done to evaluate the metabolic activity of active disease by 18F Flurodeoxyglucose (FDG) PET-CT in diagnosed cases of EPTB patients.Patients and methods: A total of 17 patients with EPTB were included in this study. FDG PET-CT scan was performed to evaluate the metabolic activity of tubercular lesions before anti-TB treatment. Clinical features, biochemical changes including ESR, WBC count, CRP, MT test and maximum standardized uptake value (SUVmax) of most intense FDG avid lesions and sizes were recorded in 18F FDG PET-CT scan.Results: All 17 patients (09 female, 08 male) had lymph node involvement, two had bone TB and two had abdominal TB. Active TB lesions showed increased FDG uptake in extra-pulmonary tubercular lesions in 16 patients. The mean SUVmax value of the involved lymph nodes were 9.4 ± 6.0 and the mean size (maximum diameter) 19.8 ± 10.4 mm (mean ± SD). One histologically proven EPTB patient had non avid lesions in FDG PET-CT scan.Conclusion: 18F FDG PET-CT scan plays an important role in the localization, extension and differentiation between active and latent TB. In this study, the metabolic activity and size of the involved tubercular lymph nodes were increased in active lesions. Increased FDG uptake in active tubercular lesions may help in treatment monitoring of EPTB. Non avid lesions in EPTB patients revealed suggested latent TB which can change further management plan. Although PET-CT is an expensive technology, application of this sophisticated imaging technique in atypical or doubtful cases of EPTB might modify the treatment plan significantly after proper evaluation of the disease status. , 18F FDG PET-CT scan will be helpful to evaluate the disease status and modification of treatment regime in non-responders cost-effectively. A nationwide large-scale study would be the better way for clinical validation.Bangladesh J. Nuclear Med. 22(1): 9-14, Jan 2019